Growth Recovery in Southern Europe : A Dozen Lessons, Old and New - Islam, Roumeen (World Bank, Washington, DC, 2016)
Greece, Ireland, Portugal, and Spain entered a period of severe economic and financial stress in the aftermath of the 2008 crisis. Their collective experience confirmed the primacy of total debt, private or public, in affecting the onset of, depth of, and recovery from economic crises. The year 2010 and the years following have demonstrated the ways in which policy responses to crisis-related downturns must be adapted when major international partners experience simultaneous growth slowdowns and markets exhibit increased risk aversion. This paper compares the recovery experience of these countries in light of recent policy debates and research on the impact of macroeconomic and structural reforms. It highlights that (a) the quality of the policies adopted to stabilize economies in the short run affects growth recovery in the long run; and (b) macroeconomic policies (fiscal and monetary) are most effective in supporting growth when they take into account structural differences between countries and when policies complement each other. The country experiences indicate that a holistic view of factors affecting investment, exports, and employment is needed to understand the impact of macroeconomic and structural reforms on output. In the absence of such a holistic view, policy may neglect to influence the binding constraints to growth.